Residual efficacy of an insecticide-coated net for the control of stored product beetles. (September 2021) - Agrafioti, Paraskevi; Arvanitakis, George; Rumbos, Christos I.; Athanassiou, Christos G.
Abstract: In the present study, the residual efficacy of an alpha-cypermethrin-coated net (Carifend®, BASF AG, Ludwigshafen, Germany) was evaluated in laboratory studies against four species of stored product insects. The insecticide-treated net was fitted into the bottom of plastic petri dishes, whereas two other sets of dishes (without net, with net without insecticide) served as controls. The insects used in the bioassays were Sitophilus oryzae, Tribolium confusum, Oryzaephilus surinamensis and Prostephanus truncatus . Adults of these species were exposed every 30 d for a total of 90 consecutive days in total. Based on the results, the insecticidal effect of the net remained at high levels during the entire experimental period, indicating its high residual effect. Among the species tested, T. confusum was the least susceptible. Carifend® can be a valuable tool for the protection of stored products against storage insects, and its use can be further examined towards this direction. Highlights: Residual efficacy of Carifend® was evaluated against four stored product insect species. Tribolium confusum was the least susceptible of the species tested. Insecticidal effect of Carifend® remained at high levels after 90 days. We estimate that this efficacy can be prolonged for more than the storage interval tested here.